An Analysis of Readiness for Implementing the Merdeka Curriculum in Physics Education - Mutmainna, Mutmainna; Usman, Usman; Helmi, Helmi; Setiawan, Trisno (Universitas Lambung Mangkurat, 2024)
This research focuses on implementing the Merdeka Curriculum, which is still relatively new and requires further adaptation in its execution. To ensure effective application, readiness for implementing the Merdeka Curriculum is crucial for each school. This study assesses the readiness for implementing the Merdeka Curriculum in physics education at high schools (SMAN) in Soppeng Regency. The research employed a descriptive approach. The findings indicate that the readiness for implementing the Merdeka Curriculum regarding teacher preparedness was 93.45%. The readiness of the teaching modules was 77.30%, which met the necessary components, while the readiness of facilities and infrastructure was 97.38%, indicating adequate resources for the curriculum’s implementation. Based on these findings, it can be concluded that high schools in Soppeng Regency were generally prepared to implement the Merdeka Curriculum for physics subjects. However, the readiness of the teaching modules was the lowest compared to teacher preparedness and facilities readiness. This could be attributed to the insufficient training that teachers had received on the Merdeka Curriculum. The implications of this research suggested the need for increased teacher training, particularly in preparing teaching modules, to ensure effective learning. Additionally, this research contributed to the literature by thoroughly examining the readiness to implement the Merdeka Curriculum, including teacher readiness, teaching modules, and facilities. Research has yet to comprehensively explore these aspects together, as most studies focus either on teacher readiness or the obstacles in implementing the Merdeka Curriculum.